First record of the genus Porcellanola László, Ronkay & Witt, 2006 (Lepidoptera, Nolidae, Nolinae) from India with description of a new species - Joshi, Rahul; Singh, Navneet; László, Gyula M.; Kuni, Nikhil (Zootaxa, 2020)
Genus Porcellanola is reported for the first time from India with description of a new species, Porcellanola sikkima Joshi, Singh & László sp. nov., (Sikkim) along with the morphotaxonomy of two more species, P. sukhothai László, Ronkay & Witt, 2006 and P. langtangi László, Ronkay & Witt, 2006. In addition, first description of the female genitalia of P. sukhothai is provided.